Visible light mediated efficient oxidative benzylic sp3 C–H to ketone derivatives obtained under mild conditions using O21. Issue 74 (25th September 2015) - Yi, Hong; Bian, Changliang; Hu, Xia; Niu, Linbin; Lei, Aiwen
<x xml:space="preserve">Abstract</x> A photooxygenation of benzylic sp3 C–H reaction has been demonstrated using O2 mediated by visible light. Various benzylic sp3 C–H bonds can be transformed into the desired ketone derivatives in moderate to good yields.